2002
DOI: 10.1159/000063907
|View full text |Cite
|
Sign up to set email alerts
|

Meyerson Phenomenon within a Nevus flammeus

Abstract: Only few reports about eczematous reactions overlying nevi flammei exist. All of them were observed in children. The description of an eczematous reaction within a congenital nevus flammeus on the left lower leg of a male adult gives reason to discuss this rare phenomenon. Eczema or inflammatory changes within a port-wine stain may mostly be a collision dermatosis with an atopic dermatitis, especially when they arise in children and are localized to the neck and face. When they are observed within a grossly vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Based on the definition of a nevus by Happle [7], in 2002 Hofer suggested that nevi flammei, which are oriented along the lines of Blaschko, similar to congenital nevi, are associated with genetic mosaicism. Thus the lesions have a certain microenvironment which differs from the surrounding skin [6]. This theory is similar to observations made by Bon and colleagues with regard to the Renbök phenomenon which is associated with alopecia areata.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Based on the definition of a nevus by Happle [7], in 2002 Hofer suggested that nevi flammei, which are oriented along the lines of Blaschko, similar to congenital nevi, are associated with genetic mosaicism. Thus the lesions have a certain microenvironment which differs from the surrounding skin [6]. This theory is similar to observations made by Bon and colleagues with regard to the Renbök phenomenon which is associated with alopecia areata.…”
Section: Discussionsupporting
confidence: 79%
“…Sidewell and Harper later expanded this theory, stating that due to vasodilatation within a nevus flammeus there was excessive pro‐inflammatory cytokine secretion which promoted the development of eczema [5]. In large nevi flammei, such as in Klippel‐Trénauny syndrome, eczema is thought to arise from stasis within the vessels as in stasis dermatitis [6]. This hypothesis is supported by the observation that after laser therapy with a dye laser, there is improvement or healing of the eczema.…”
Section: Discussionmentioning
confidence: 99%
“…Although PWS‐associated dermatitis has been reported (5–8), the underlying pathogenesis remains to be elucidated. Sidwell et al (6) postulated that PWS‐associated dermatitis may be caused by an abnormal production of cytokines causing inflammatory changes in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported the development of an eczematous dermatitis within PWS (5–8). Patients present with scaling, pruritic, excoriated, and inflammatory lesions that tend to occur solely or most severely within the borders of the PWS.…”
mentioning
confidence: 99%
See 1 more Smart Citation